Adaptation of a Diverse Simian Immunodeficiency Virus Population to a New Host Is Revealed through a Systematic Approach to Identify Amino Acid Sites under Selection - Vanderford, Thomas H.; Demma, Linda J.; Feinberg, Mark B.; Staprans, Silvija I.; Logsdon, John M. (Molecular biology and evolution, 2007)
Simian immunodeficiency viruses (SIV) have had considerable success at crossing species barriers; both human immunodeficiency virus (HIV)-1 and HIV-2 have been transmitted on multiple occasions from SIV-infected natural host species. However, the precise evolutionary and ecological mechanisms characterizing a successful cross-species transmission event remain to be elucidated. Here, in addition to expanding and clarifying our previous description of the adaptation of a diverse, naturally occurring SIVsm inoculum to a new rhesus macaque host, we present an analytical framework for understanding the selective forces driving viral adaptation to a new host. A preliminary analysis of large-scale changes in virus population structure revealed that viruses replicating in the macaques were subject to increasing levels of selection through day 70 postinfection (p.i.), whereas contemporaneous viruses in the mangabeys remained similar to the source inoculum. Three different site-by-site methods were employed to identify the amino acid sites responsible for this macaque-specific selection. Of 124 amino acid sites analyzed, 3 codons in V2, a 2–amino acid shift in an N-linked glycosylation site, and variation at 2 sites in the highly charged region were consistently evolving under either directional or diversifying selection at days 40 and 70 p.i. This strong macaque-specific selection on the V2 loop underscores the importance of this region in the adaptation of SIVsm to rhesus macaques. Due to the extreme viral diversity already extant in the naturally occurring viral inoculum, we employed a broad range of phylogenetic and numerical tools in order to distinguish the signatures of past episodes of selection in viral sequences from more recent selection pressures.